ASSOCIATION BETWEEN PERIPHERAL ARTERIAL DISEASES AND METABOLIC SYNDROME IN PATIENTS WITH TYPE 2 DIABETES FROM NORTHWESTERN ALGERIA - Imane Bouragba; Mustapha Diaf (Journal of Postgraduate Medical Institute, 2023)
Objective: This study aims to explore the correlation between peripheral arterial diseases (PAD) and individual components of metabolic syndrome among type 2 diabetic patients. Methodology: Between December 2019 and March 2022, we carried out a cross-sectional investigation involving 191 patients diagnosed with type 2 diabetes. These patients were admitted to the internal medicine department at of the Public Hospital Establishment of "Ben Badis" and the Public Establishment of Local Health “Larbi Ben M'hidi Diabetes Centre” of Sidi-Bel-Abbes, Algeria. The criteria established by NCEP ATPIII (National Cholesterol Education Program Adult Treatment Panel III) were employed to define the presence of metabolic syndrome (MetS). Diagnosis of peripheral arterial disease (PAD) was based on Angiography and an ankle-brachial index (ABI) below 0.9. Results: Of the 191 diabetic individuals, 47.1% had PAD and 78.5% had MetS; 52.66% of MetS patients developed PAD. Significant differences (p<0.05) in age, LDL, TG, CRP, serum chloride, and fibrinogen were noted between PAD and NPAD groups. Causal associations (p<0.05) were found between PAD and male gender, obesity, hypertension, dyslipidemia, inactivity, and MetS. PAD increased with MetS anomalies. Strongest PAD risks were low HDL, high TG, and blood sugar cluster (OR=10.75), followed by high waist circumference, TG, blood pressure, and blood sugar cluster (OR=8.361). Conclusion: This study reveals a strong MetS-PAD association and highlights how specific MetS components independently influence PAD occurrence in adult type 2 diabetes patients.